2018
DOI: 10.2516/ogst/2017043
|View full text |Cite
|
Sign up to set email alerts
|

Flow Simulation Using Local Grid Refinements to Model Laminated Reservoirs

Abstract: Super-giant carbonate fields, such as Ghawar, in Saudi Arabia, and Lula, at the Brazilian pre-salt, show highly heterogeneous behavior that is linked to high permeability intervals in thin layers. This article applies Local Grid Refinements (LGR) integrated with upscaling procedures to improve the representation of highly laminated reservoirs in flow simulation by preserving the static properties and dynamic trends from geological model. This work was developed in five main steps: (1) define a conventional coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…3.1 Green steps 1. Reservoir characterization under uncertainties (to build models, develop scenarios, and estimate probabilities) (Correia et al, 2015(Correia et al, , 2018a(Correia et al, , 2018bMahjour et al, 2019). This crucial step requires a multidisciplinary approach to consider all possible uncertainties: reservoir, fluid, economic, and operational attributes.…”
Section: Methodsmentioning
confidence: 99%
“…3.1 Green steps 1. Reservoir characterization under uncertainties (to build models, develop scenarios, and estimate probabilities) (Correia et al, 2015(Correia et al, , 2018a(Correia et al, , 2018bMahjour et al, 2019). This crucial step requires a multidisciplinary approach to consider all possible uncertainties: reservoir, fluid, economic, and operational attributes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the same authors developed a work in 2018 (Correia et al, 2018) integrating the LGR technique in high permeability layers ("super-k" layers) besides the well locations. They associate the LGR with upscaling techniques to better represent highly laminated and fractured reservoirs in the flow simulation.…”
Section: Well Calibration In Simulation Models Of Nfrmentioning
confidence: 99%
“…(5.2) It is concluded that the well static and dynamic data are impacted by the DFN permeability upscaling method and the grid-scale. Consequently, these aspects can affect the reservoir development and management phase or mask the reservoir characterization uncertainties (Correia et al, 2018;Ahmed-Elfeel and Geiger, 2012). Therefore, it is important to carry out a deeper fracture system study when setting new wells in DK simulation models, analyzing the appropriate DFN upscaling method and fidelity scale.…”
Section: Summary Of Well Static and Dynamic Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Definição de incertezas (fluido, reservatório, económicas, operacionais, etc.) e suas probabilidades (Correia et al, 2015(Correia et al, , 2018a(Correia et al, , 2018bMahjour et al, 2019).…”
Section: Desenvolvimento E Gerenciamento De Reservatórios Em Malha Fe...unclassified